A REVIEW OF 10% INTEREST PARTICIPATION MANAGEMENT BASED ON THE PANCASILA ECONOMIC SYSTEM - Salsabila, Alfian Nur (JURNAL SETIA PANCASILA, 2023)
This study aimed to identify the ideal arrangement and concept for the management of 10% interest participation in the oil and gas sector. Writing is done by reviewing library data, in the form of laws and regulations, books, articles, journals, and others. The results of the study show that arrangements regarding the management of the 10% interest participation are currently not implemented optimally and comprehensively, so by reconceptualizing the management of interest participation in a way that ismore integrative and in line with the Pancasila economic system, it will have positive implications for areas where exploration and exploitation activities have been carried out. This new concept of interest participationmanagement will be more equitable for oil and gas producing regions and prioritize joint ventures based on the principle of kinship for the prosperity of the people.